2019
DOI: 10.1101/616656
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

An in vitro model maintaining taxon-specific functional activities of the gut microbiome

Abstract: The gut microbiome is a new target for therapeutics. In vitro high-throughput culture models could provide time-and-cost saving solutions to discover microbiome responses to drugs. Unfortunately, there has been no report of in vitro models capable of maintaining functional and compositional profiles resembling the in vivo gut microbiome. Here, we developed and validated a high-throughput culturing model named Mipro to maintain individuals' microbiomes. The Mipro model quintupled viable bacteria count while mai… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(37 citation statements)
references
References 59 publications
0
37
0
Order By: Relevance
“…Metformin, a drug widely used in the treatment of type II diabetes, has previously been shown to alter gut microbiome taxonomic composition and functionality (De La Cuesta-Zuluaga et al, 2017; Ma et al, 2018; Li et al, 2019). In our study, we identified metformin-induced alterations to the same pathways as other studies, for example a decrease in fatty acid biosynthesis [PATH:KO00061] (Li et al, 2019), decrease in nitrogen metabolism [PATH:KO00910], increase in oxidative phosphorylation [PATH:KO00190], enrichment in lipopolysaccharide biosynthesis [PATH:KO00540] (Ma et al, 2018), and an increase in tRNA biosynthesis [BR:KO03016]. Metformin has also been shown to reduce folate metabolism (Cabreiro et al, 2013), thus lower “one carbon pool by folate” GSVA scores in metformin treated samples are expected.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Metformin, a drug widely used in the treatment of type II diabetes, has previously been shown to alter gut microbiome taxonomic composition and functionality (De La Cuesta-Zuluaga et al, 2017; Ma et al, 2018; Li et al, 2019). In our study, we identified metformin-induced alterations to the same pathways as other studies, for example a decrease in fatty acid biosynthesis [PATH:KO00061] (Li et al, 2019), decrease in nitrogen metabolism [PATH:KO00910], increase in oxidative phosphorylation [PATH:KO00190], enrichment in lipopolysaccharide biosynthesis [PATH:KO00540] (Ma et al, 2018), and an increase in tRNA biosynthesis [BR:KO03016]. Metformin has also been shown to reduce folate metabolism (Cabreiro et al, 2013), thus lower “one carbon pool by folate” GSVA scores in metformin treated samples are expected.…”
Section: Discussionmentioning
confidence: 99%
“…We adopted an ex vivo microbiome assay, termed RapidAIM (rapid assay of individual’s microbiome) (Li et al, 2019) to assess the direct effects of the histone deacetylace (HDAC) inhibitor suberoulanilide hydroxamic acid (SAHA) on a human microbiome. Briefly, in a RapidAIM assay, a human gut microbiome (fecal) sample was cultured for 24 hours in anaerobic conditions in control conditions with dimethyl sulfoxide (DMSO) and treatment conditions with a low (0.125mg/ml), or high concentration of SAHA (0.25mg/ml).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Protein was pelleted by centrifugation at 16000g, 4 °C, 10 min and washed with the ice-cold acetone two times. For the in-solution trypsin digestion, the procedure was performed as the previously report 43 . Briefly, the resulting protein was dissolved in 50 mM ammonium bicarbonate and 8 M urea solution, reduced in 5 mM dithiothreitol (DTT) (56 °C, 30 min), and alkylated by with 10 mM iodoacetamide (25 °C, 40 min in the dark).…”
Section: Methodsmentioning
confidence: 99%